Human immunodeficiency virus type 1 expression in the central nervous system correlates directly with extent of disease. - Weiser, B (1990)
To investigate human immunodeficiency virus type 1 (HIV-1) pathogenesis in infected individuals and examine the correlation of HIV-1 expression with extent of clinical and pathologic disease, we studied spinal cords from acquired immunodeficiency syndrome patients with a wide range of spinal cord pathology. By performing in situ hybridization with HIV-1-specific riboprobes, we detected HIV-1 RNA in all 10 cords from acquired immunodeficiency syndrome patients with a common, characteristic pathologic entity called vacuolar myelopathy but not in 10 control cords from HIV-1-infected and uninfected patients. In the cords from individuals with vacuolar myelopathy, the level of HIV-1 RNA expression correlated directly with extent of spinal cord pathology and clinical findings. These data support a role for HIV-1 in the pathogenesis of tissue damage and related clinical disease in infected individuals.